Sounding Identity: A Technical Analysis of Singing Styles in the Traditional Music of Sub-Saharan Africa - Alfred Patrick Addaquay (Arts, 2025)
This article presents an in-depth examination of the technical and cultural dimensions of singing practices within the traditional music of sub-Saharan Africa. Utilizing an extensive body of theoretical and ethnomusicological research, comparative transcription, and culturally situated observation, it presents a comprehensive framework for understanding the significance of the human voice in various performance contexts. The study revolves around a tripartite model—auditory clarity, ambiguous auditory clarity, and occlusion—that delineates the varying levels of audibility of vocal lines amidst intricate instrumental arrangements. The article examines case studies from West, East, and Southern Africa, highlighting essential vocal techniques such as straight tone, nasal resonance, ululation, and controlled (or delayed) vibrato. It underscores the complex interplay between language, melody, and rhythm in tonal languages. The analysis delves into the influence of sound reinforcement technologies on vocal presence and cultural authenticity, positing that PA systems have the capacity to either enhance or disrupt the equilibrium between traditional aesthetics and modern requirements. This research is firmly rooted in a blend of African and Western theoretical frameworks, drawing upon the contributions of Nketia, Agawu, Chernoff, and Kubik. It proposes a nuanced methodology that integrates technical analysis with cultural significance. It posits that singing in African traditional music transcends mere expression, serving as a vessel for collective memory, identity, and the socio-musical framework. The article concludes by emphasizing the enduring strength and flexibility of African vocal traditions, illustrating their capacity for evolution while preserving fundamental communicative and artistic values.